1987
DOI: 10.1111/j.1476-5381.1987.tb10299.x
|View full text |Cite
|
Sign up to set email alerts
|

pH‐dependent stimulation by Ca2+ of prostacyclin synthesis in rat aortic rings: effects of drugs and inorganic ions

Abstract: 1 Fresh rat aortic rings were incubated in HEPES-buffered salt solutions. Extracellular Ca24 stimulated the production of prostacyclin (PGI2), as determined by radioimmunoassay of its stable hydrolysis product 6-oxo-prostaglandin F,. This action of Ca24 was modified by H4 over the pH range 8.0-6.5. Stimulation by calcium ionophore A23187 was not pH-dependent.2 In parallel incubations of aortic rings with 4 Ca2", followed by washing in the presence of La3, tissue uptake of 45Ca2" increased progressively as extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 39 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…In contrast to piglet pulmonary vessels, NO did not contribute to alkalosisinduced vasodilation in the rabbit (31) or rat (32) lung. PGI 2 synthesis, like NO synthesis, is enhanced by increased endothelial cell cytosolic Ca 2+ (33). These findings reflect the interspecies differences in dominant endothelium-derived modulator synthesis.…”
Section: Respiratory Alkalosissupporting
confidence: 47%
“…In contrast to piglet pulmonary vessels, NO did not contribute to alkalosisinduced vasodilation in the rabbit (31) or rat (32) lung. PGI 2 synthesis, like NO synthesis, is enhanced by increased endothelial cell cytosolic Ca 2+ (33). These findings reflect the interspecies differences in dominant endothelium-derived modulator synthesis.…”
Section: Respiratory Alkalosissupporting
confidence: 47%
“…Besides the NO story for the vasodilatory mechanism of alkalization, it has been demonstrated that alkalosis enhances prostacyclin synthesis (15,22,32). However, we could not detect augmentation of cyclooxygenase-1 mRNA and protein expression during alkalosis in our assay methods (unpublished observation).…”
Section: Discussionmentioning
confidence: 71%
“…Aortic rings were prepared by methods similar to those described previously (Bunting et al, 1976;Ritter et al, 1987 HEPES were the same as in the other protocol. Amiloride and the analogues studied were prepared specially for this study by previously published methods (Cragoe et al, 1967;.…”
Section: Aortic Ring Incubationsmentioning
confidence: 99%
“…PGI2 synthesis is inhibited by 8-(N,N-diethylamino)octyl 3,4,5-trimethoxybenzoate (TMB8) (Brotherton & Hoak, 1982;Ritter, 1984) an antagonist of intracellular Ca2" mobilisation (Malagodi & Chiou, 1974). In contrast, drugs that influence voltage-dependent Ca2+ channels have variable actions on PGI2 synthesis in different preparations and are often only effective at high concentration (Whorton et al, 1984;Jeremy et al, 1985;1986;Hassid & Oudinet, 1986;van de Velde et al, 1986;Mehta et al, 1986;Ritter et al, 1987). In rat aortic rings, stimulation ofPGI2 synthesis 'Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation